(untitled) (American Journal of Islam and Society, 2004)
Followers of the Islamization of Knowledge project probably know the work of Ziauddin Sardar best for its trenchant critique of that project. Yet the prolific British-Pakistani intellectual has written thoughtfully on topics ranging from the social consequences of science and technology and the future development of Muslim societies to cultural studies and the impact of postmodernism on religious belief. Since Sardar’s work is scattered across books, academic journals, and science and news magazines, the Reader is a most welcome compendium that showcases the breadth of his engagements. The book contains 20 selections, which are divided almost equally into three sections; the editors’ introduction, which I discuss below; and a working bibliography of Sardar’s writings and index, both of which are very useful additions ...